Cordierite megacrysts in felsic gneiss from Botunnuten in southern Lützow-Holm Complex, East Antarctica - Baba, Sotaro; Ohshiro, Seira; Hokada, Tomokazu; Kamei, Atsushi; Kitano, Ippei; Motoyoshi, Yoichi (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object